Analisis Tata Niaga Kacang Tanah Studi kasus di Desa Labuaja, Kecamatan Cenrana, Kabupaten Maros - Damayanti Damayanti; Arifin Arifin; Mohammad Anwar Sadat (Jurnal Agribis, 2023)
The marketing aspect is very important in marketing agricultural products. If the marketing mechanism is good, then all parties involved will benefit. A farm with good productivity will fail if the marketing is not good. Marketing channels have an important role in farmers' lives. Peanut plants are one of the plants that have long been known by the public since ancient times. Until now, the cultivation of peanuts for some residents has been carried out by the Indonesian people. The plant now has promising prospects because it has an economy that can be cultivated. The purpose of this study was to determine the Peanut Marketing Channel in Labuaja Village, Cenrana District, Maros Regency for three months, namely March - June 2022. The types and sources of data used in this study were primary and secondary data. Data collection techniques used are observation and interviews. The population of this research are all farmers who cultivate peanuts and traders. The sample of farmers was taken as many as 15 people with simple random sampling method. For traders, it consists of 1 small trader and 1 big trader who is taken intentionally (Purposive). The analysis used is descriptive quantitative data analysis. The results of the research are that there are three marketing channels for Peanuts in Labuaja Village, Cenrana District, Maros Regency, namely: (1) Channel I: Farmers to Consumer Farmers, (2) Channel II: Farmers Wholesale to Consumer and (3) Channel III: Farmers to Wholesalers to Traders Retailers to Consumers. The marketing margin of peanuts in Labuaja Village, Cenrana District, Maros Regency is Rp. 0 on Channel I, Rp. 3,000 on channel II and Rp. 5,000 On Channel III